Spectroscopic evaluation of carbohydrate levels in cell line treated with red microalgal polysaccharides. Issue 2 (2003) - Erukhimovitch Erukhimovitch, Vitaly Vitaly; Talyshinsky Talyshinsky, Marina Marina; Souprun Souprun, Yelena Yelena; Huleihel Huleihel, Mahmoud Mahmoud
Abstract : Sulfated polysaccharides obtained from red microalgae proved to be as potent antiviral agents against various viruses. The huge molecular weight of these polysaccharides contributed much to the difficulty in explaining and understanding the mechanism of their activity against internal steps in the replication cycle of these viruses. In the present study we used microscopic Fourier-Transform Infrared Spectroscopy (FTIR) to investigate: (a) possible penetration of these polysaccharides into the treated cells, (b) effect of the polysaccharides treatment on some metabolic changes in these cells. Our results show a rapid accumulation of carbohydrates in the treated Vero cells. The carbohydrates level in these cells increases continuously after treatment during the entire experiment time period. In addition, we noted a gradual shift of PO2 -ionized symmetric stretching peak of Vero cells to the position found in primary cells as a result of the continuous treatment with the microalgal polysaccharides.